2019
DOI: 10.1111/jcmm.14755
|View full text |Cite
|
Sign up to set email alerts
|

Role of VEGFR‐1 in melanoma acquired resistance to the BRAF inhibitor vemurafenib

Abstract: The vascular endothelial growth factor receptor‐1 (VEGFR‐1) is a tyrosine kinase receptor frequently expressed in melanoma. Its activation by VEGF‐A or placental growth factor (PlGF) promotes tumour cell survival, migration and invasiveness. Moreover, VEGFR‐1 stimulation contributes to pathological angiogenesis and induces recruitment of tumour‐associated macrophages. Since melanoma acquired resistance to BRAF inhibitors (BRAFi) has been associated with activation of pro‐angiogenic pathways, we have investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…A range of genetic mutations have been identified as causing acquired BRAF resistance (recently reviewed by Tian and Guo and summarized in Table 1 ) [ 11 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A range of genetic mutations have been identified as causing acquired BRAF resistance (recently reviewed by Tian and Guo and summarized in Table 1 ) [ 11 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ...…”
Section: Resultsmentioning
confidence: 99%
“…Overexpressed genes in BRAF inhibitor-resistant cells are often associated with growth factors and their receptors, cell adhesion molecules and extracellular matrix binding [ 84 ]. Common mutations involve effects on receptor tyrosine kinases (RTKs), such as epidermal growth factor receptor (EGFR), platelet-derived growth factor receptor (PDGFR), hepatocyte growth factor (HGF), or insulin-like growth factor (IGF) receptor, which in turn activate parallel pathways [ 11 , 19 , 20 , 25 , 29 , 58 , 59 , 84 , 85 , 86 ]. Research has shown extensive redundancy in RTK-mediated signaling pathways, whereby a broad range of widely expressed RTKs are upregulated in cells with BRAF inhibitor resistance [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, vemurafenib-resistant melanoma cells expressing VEGFR-1 showed a higher invasive behavior, compared to melanoma cells susceptible to the BRAFi. Accordingly, treatment with D16F7 markedly reduced ECM invasion by resistant cells in response to VEGF-A and PlGF, suggesting that VEGFR-1 blockade in combination with the BRAFi might delay the acquisition of a resistance phenotype [161].…”
Section: Melanomamentioning
confidence: 98%
“…Moreover, triple VEGFRs downregulation synergized with standard chemotherapy (5-fluorouracil and cisplatin combination) in vivo [191]. high coexpression of VEGFR-1 and MMP9 act as prognostic marker [115,116] -The VEGF-B186 is frequently upregulated compared to the VEGF-B167 and its expression correlates with cancer growth and invasiveness [110] -VEGF-A secretion is reduced by miR-199a-3p [111] -PlGF in vivo blockade results in normalization of tumor-associated vessels, reduced tumor nodule formation and increased survival [112,113] -VEGF-B favors molecular and morphological alterations of EMT [115] -VEGFR-1 and VEGFR-2 expression on endothelial cells is reduced by miR-199a-3p [111] -VEGFR-1 is required for the vascularization of liver metastases from renal cell carcinoma [124] -In high-grade glioma specimens, VEGFR-1 is expressed at significantly higher levels than in low-grade glioma [146] -VEGF-A-and PlGF-mediated activation of VEGFR-1 stimulates tumor growth and angiogenesis in an in vivo preclinical glioma model [148] -Glioblastoma cells (cell lines and tumor specimens from patients) and primary cultures of glioblastoma stem cells express VEGFR-1 [145] -VEGF-A expression is higher in glioblastoma than in low-grade gliomas and plays a role in the switch to a highly vascularized tumor [31] -GAMs contribute to tumor progression and resistance to anti-VEGF-A therapy [149][150][151][152][153] - -PlGF induces tumor growth, vascularization, and metastases in a preclinical in vivo model [162] -PlGF induces resistance to temozolomide through NF-κB activation [163] -The sVEGFR-1/VEGFR-1 transcript ratio decreases in cutaneous metastases compared to primary tumors, due to decrease of sVEGFR-1 mRNA levels [36] -Upregulation of VEGFR-1 contributes to resistance toward BRAFi [161] Bone Osteosarcoma Lungs, other bones, and lymph nodes -Increased VEGF-A serum levels are associated with enhanced vessel density in the tumor and decreased survival [170][171][172] -VEGF-A gene polymorphisms +936C/T and -634 G/C are associated with the risk of developing osteosarcoma …”
Section: Pancreatic Cancermentioning
confidence: 99%
“…Melanoma patients harboring the BRAF V600E mutation display primary resistance. Prolonged treatment with BRAF/MEK inhibitors induces acquired resistance (Atzori et al, 2020). These reports suggest that targeting molecular reprogramming induced by BRAF/MEK inhibitors is necessary to treat melanomas.…”
Section: The Mechanisms Of Anti-cancer Drug Resistance In Melanomamentioning
confidence: 99%